2020
DOI: 10.1007/s10640-020-00428-x
|View full text |Cite
|
Sign up to set email alerts
|

Welfare and Trade Effects of International Environmental Agreements

Abstract: We analyse the welfare effects of environmental policy arising from the formation of an international environmental agreement on the participating and non-participating countries and thus shed light on the potential incentives for a country to join such an agreement. Within a N-country Q-goods general equilibrium framework under free-trade conditions, we consider unilateral and cooperative policy settings and, within the latter, country-specific and fully harmonized policies within the agreement. A key result … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 30 publications
(42 reference statements)
0
2
0
Order By: Relevance
“…This includes environmental benefits, as well as economic benefits, if some parts of a ratifier's production are relocated to a non-ratifier country. Based on their modeling results, Montagna et al (2020) highlighted a potential side-effect, namely international environmental agreements may lead to a welfare reduction in the non-participating countries.…”
Section: Effect Of Climate Policy Measures On Trade and Economic Welfarementioning
confidence: 99%
“…This includes environmental benefits, as well as economic benefits, if some parts of a ratifier's production are relocated to a non-ratifier country. Based on their modeling results, Montagna et al (2020) highlighted a potential side-effect, namely international environmental agreements may lead to a welfare reduction in the non-participating countries.…”
Section: Effect Of Climate Policy Measures On Trade and Economic Welfarementioning
confidence: 99%
“…The research of Montagna, Pinto and Vlassis (2020) on the trade effects of international environmental agreements on the welfare of the countries has shown that introduction of the agreements can reduce the level of welfare in the non-participating countries due to the trade creation and trade diversion effects of the policy. Thus, the terms-of-trade effects of EP are substantial channel affecting the incentives of the countries to join an environmental agreement and can deteriorate the pollution haven effect.…”
Section: The Impact Of Ep On Export Of the Countriesmentioning
confidence: 99%
“…The idea of an IEA providing club goods to its parties is usually treated as a policy proposal that still lacks an empirical manifestation. As a consequence, the literature on environmental club is mainly based on theoretical inquiries, survey experiments, numerical simulations, and agent-based models (e.g., Cirone & Urpelainen, 2013;Eichner & Pethig, 2015;Gampfer, 2016;Hagen & Schneider, 2017;Hovi et al, 2019;Kemfert, 2004;Lessmann et al, 2009;Montagna et al, 2019;Saelen, 2016;Sprinz et al, 2018). 3 1 3…”
mentioning
confidence: 99%